Targeting Debt in Pakistan: A Structural Macro-Econometric Model - Fatemah, Ambreen; Haq, Ahsan ul (iRASD Journal of Economics, 2024)
Unsustainable debt levels pose serious economic risks, potentially leading to financial instability when repayments become challenging. This paper investigates the intricate dynamics of Pakistan’s debt. It aims to assess its sustainability within a broader eclectic and dynamic framework of responsible fiscal management using macro-econometric analysis. A structural macro-econometric model (MEM) based on five blocks has been developed, i.e., Government, Price, Real, Monetary, and External sectors. Moreover, it comprises sixteen behavioral equations along with ten identities. The Generalized Method of Moments (GMM) has been used to estimate the system of behavioral equations and identities to solve the endogeneity problem, while the Guass-Seidel algorithm is used for model simulation purposes, including dynamic & stochastic simulations. Forecasting has been done from 2023 – 2030. Moreover, three main policy variables, i.e., inflation, exchange rate, and government expenditures, have been given shocks to evaluate their impact on future external borrowing, interest payments along with imports, exports, and net foreign and domestic assets. The results revealed that an effective monetary & fiscal policy must be designed to stabilize the economic conditions to manage external debt and repayments effectively. Moreover, to cope with unsustainable debt conditions, it is required to follow strict fiscal discipline via designing & adhering to a budget that prioritizes inflationary controls and responsible spending practices.